Skull Base Surgery of the Posterior Fossa (Springer International Publishing, 2018)
This text provides a comprehensive and contemporary overview of surgical approaches to lesions of the posterior fossa. It will serve as a resource for neurosurgeons and otologists who treat patients with tumors and vascular diseases of the posterior fossa. It provides a concise review of surgical strategies that address the most important pathologies affecting the posterior fossa. It is richly illustrated with photographs of the surgical strategies covered. All chapters are written by experts with world-wide recognition for their contributions in their respective subspecialty. Skull Base Surgery of the Posterior Fossa will be of great utility to Neurosurgeons, Otolaryngologists, and Radiation Therapists with an interest in diseases that affect the posterior fossa, as well as Senior Residents in Neurosurgery and Otolaryngology, and Fellows of Skull Base Surgery and Otology.